An Analysis of Wage Differentials between Full- and Part-Time Workers in Spain - Raul Ramos; Esteban Sanromá; Hipólito Simón (Institute for the Study of Labor (IZA), 2015)
This research examines wage differences between part-time and full-time workers using microdata from the Spanish Structure of Earnings Survey. The main contribution of the paper is related to the analysis of differences along the wage distribution using econometric decomposition methods and introducing a regional perspective. The evidence shows that part-time workers in Spain experience a significant wage disadvantage. This disadvantage is worse in the case of female workers and it is not homogenous along the wage distribution, being comparatively more relevant for the most qualified women and becoming positive for the most qualified men. However, the disadvantage is practically explained by the endowments of characteristics, with a leading role of segregation of part-time workers in low-wage firms. From a regional perspective, although in the majority of the regions wage differences tend to be explained by endowments of characteristics, there are several regions where the unexplained part of the differential is significant, particularly in the case of male workers. These regional differences seem to be related to differences in the market power of firms at the regional level.
Keywords: J31; J22; J41; R23; 330; part-time work; wage gap; regional differences